الفكر الديني في مشروع مؤسسة مؤمنون بلا حدود : قرأة نقدية - Hirreche Baghdad Mohamed (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2022)
The religious phenomenon becomes a subject of reflection from the moment it is practiced by human beings, because it must be understood, explained and interpreted ... The revelation, the rituals and the teachings ... are fixed in sacred texts , these are the object of conservation, reading and questioning. And because the contexts in which they evolve and develop are historical, this constantly poses the modalities of harmonization and application of the texts and the way of living the faith in the present without completely breaking with the faith of the first founders, which leads to